The effect of dehydrated food waste (DFW) and Leucaena leucocephala for pregnant rabbit does and preweaners permormance - Hamdan, Arif Zakwan (2016)
Daily, human generates large quantities of food waste in restaurants, hotels, grocery stores, universities and even prisons. Large amount of food waste will creates pollution and need lots of works to dispose them. There will be air pollution and pollution to people around. Eventually, if there are no actions taken by human, diseases can spread and can harm human being. Dehydrated Food Waste (DFW) is one kind of solution for people to generate extra income and reduce the cost to dispose the food waste. Leucaena is one of fibre source for rabbit feed. Fresh or dried Leucaena leucocephala or leaf meal improves feed intake, feed efficiency and animal performance in rabbits. The combination of DFW with Leucaena in form of pellet will produce a high quality of rabbit feed and be fed to them.The objectives for this study are to identify the most suitable combination of fibre and DFW for mothering ability in rabbit doe. Next, to determine the quality of dehydrated food waste as source of energy in rabbit doe. Additionally, it is to evaluate the performance of pre-weaning rabbits nurse by rabbit doe. The study was conducted in a rabbit farm in Dengkil, and total of nine doe rabbits were used during this study. Age of rabbits was around 17-19 months old and average weight was 3.15kg. All of the rabbits are from New Zealand White breed. All of the rabbits were 2-3 weeks pregnant in initial state of experiment. There are three parameters used in this experiment which are T1- using commercial feed, T2- DFW(50%) + Leucaena(50%), and T3- DFW(60%) + Leucaena(40%). The percentage of crude protein in Leucaena is 14.7, while in DFW is 12.76. Combination in T2 has 13.72% and T3 has 14.11% crude protein. Crude fibre in Leucaena is 10.61% and in DFW is 9.81%. Combination in T2 has 10.08% and T3 has 9.69% crude fibre. The values of crude protein and crude fibre in T2 and T3 are lower than commercial feed which is 18.4% crude protein and 14.2 crude fibre. For rabbit doe, T2 has the highest mean weight (3.085kg) followed by T3 (2.943kg) and T1 (2.925kg). T2 is significantly different with T1 and T3. However, there is no significant different between T1 and T3. For kits weight per mother, T1 has the highest weaning weight (2.934kg) followed by T2 (2.886kg) and T3 (2.776kg). There is no significant different in all treatments. In conclusion, this result showed that different percentage of fibre and concentrate combination will have different effect on rabbit’s milk production and mothering ability.